Massive transformation in Ti–6Al–4V additively manufactured by selective electron beam melting. (1st February 2016) - Lu, S.L.; Qian, M.; Tang, H.P.; Yan, M.; Wang, J.; StJohn, D.H.
Abstract: The occurrence of the β (bcc) to αm (hcp) massive transformation in Ti–6Al–4V (wt.%) during additive manufacturing (AM) by selective electron beam melting (SEBM) has been identified. A variety of patch-shaped massive grains including both grain boundary (GB)-crossing and non-GB-crossing instances were characterised and their formation temperature and growth rate were estimated. In contrast to conventional Ti–6Al–4V, the massive grains in SEBM-fabricated Ti–6Al–4V consist of ultrafine lamellar α and β phases (100 nm wide β strips) due to in-situ decomposition of the massive grains during AM. The resulting ultrafine α-β lamellae obey the typical Burgers orientation relationship established for the lamellar α-β structure in conventional Ti–6Al–4V. These findings show that the β (bcc) to αm (hcp) massive transformation significantly contributes to development of the Ti–6Al–4V microstructure during AM by SEBM, providing an alternative microstructural design strategy for AM of Ti–6Al–4V and other titanium alloys. Graphical abstract: (a) EBSD colour inverse pole figure (IPF) showing both non-GB-crossing (i.e.③) and GB-crossing (i.e. ④ and ⑤) massive phase grains. (b) Multiple-spot TEM BF image showing the ultra-fine α-β microstructures within the massive phase grain. The inset in (a) is an EBSD band-contrast map showing the original prior-β GB. The side arrow in (a) represents the SEBM building direction.